Pd-Nanoparticles-Catalyzed C(sp2)–H Arylation for the Synthesis of Functionalized Heterocycles: Recent Progress and Prospects - Sunny, Steeva; Maingle, Mohit; Sheeba, Loddipalle; Pathan, Firojkhan Rajekhan; J., Gowri Sankar; Juloori, Harika; Gadewar, Sainath Ganesh; Seth, Kapileswar (Synthesis, 2023)
Transition-metal-nanoparticles-catalyzed C–H activation/functionalization is a prominent topic in contemporary research, enabling the functionalization of privileged heterocyclic scaffolds that hold a significant space in the scientific community due to their immense applications in materials science and in medicinal, natural product, and agricultural chemistry. Among transition-metal-based nanoparticles, Pd nanoparticle catalysis has emerged as the most attractive tool for promoting a wide array of practical synthetic transformations of heterocycles. In the last few years, the catalytic application of Pd nanoparticles in C–H functionalization has gained popularity in generating relatively inaccessible bonds with a high degree of selectivity and efficiency via the activation of surface metal atoms at the nanoscale level. The quantum size effect of nanoparticles offers a large surface area, with typically many easily accessible active sites/unit areas. These unique characteristics of nanoparticles are considered primary factors of enhanced catalytic activity compared to bulk materials. The nanoparticle catalysts anchored on solid-supports plus unsupported types (e.g., magnetic nanoparticles) allow easy separation from the reaction mixture, enabling recycling multiple times, which contributes notably to sustainable management and cost efficiency of a production process. In the current review, we discuss Pd-nanoparticles-catalyzed C(sp2)–H arylation for the synthesis of functionalized heterocycles, covering literature reports from 2010 to 2021. The preparation of Pd nanoparticles and the mechanistic realizations in their corresponding reactions are also explained briefly.1 Introduction2 Arylation of Heterocyclic Scaffolds2.1 Synthesis of Functionalized Indole Derivatives2.2 Synthesis of Functionalized (Benzo)thiazole/Benzoxazole Derivatives2.3 Synthesis of Functionalized Triazoles2.4 Synthesis of Functionalized Pyridines and Related Scaffolds2.5 Synthesis of Functionalized Furan, Thiophene and N-Methylpyrrole Scaffolds2.6 Synthesis of Functionalized Multiple Heterocycles via Single-Step Strategies3 Conclusions
Keywords: Pd nanoparticles; binary nanoclusters; solid-support; heterogeneity; C(sp2)–H arylation; heterocycles; leaching; recoverability and recyclability